Electron hopping through proteins - Warren, Jeffrey J. (2012)
Biological redox machines require efficient transfer of electrons and holes for function. Reactions involving multiple tunneling steps, termed “hopping,” often promote charge separation within and between proteins that is essential for energy storage and conversion. Here we show how semiclassical electron transfer theory can be extended to include hopping reactions: graphical representations (called hopping maps) of the dependence of calculated two-step reaction rate constants on driving force are employed to account for flow in a rhenium-labeled azurin mutant as well as in two structurally characterized redox enzymes, DNA photolyase and MauG. Analysis of the 35 Å radical propagation in ribonucleotide reductases using hopping maps shows that all tyrosines and tryptophans on the radical pathway likely are involved in function. We suggest that hopping maps can facilitate the design and construction of artificial photosynthetic systems for the production of fuels and other chemicals.